Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Kemampuan Berpikir Logis Matematis Siswa pada Materi Program Linier - Prangga Assmarqandi; Laila Hayati; Hapipi Hapipi (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This research aims to determine the effect of problem-based learning model on student’s mathematical logical thinking abilities and the amount of it. To achieve the goals, this research used post-test only control group design. This research was held in class XI-IPA of SMAN 1 Sekotong and consist of 60 students which divided into two classes. By considering the post-test only control group design which requires a control group and the experimental group, used saturated sampling technique that took the whole population as the sample. The members of the population were all students of class XI-IPA of SMAN 1 Sekotong which divided into two classes XI-IPA 1 and XI-IPA 2. The instruments were used to measure the student’s logical thinking ability consist of four description. The measurement of the logical thinking ability was measured after the implementation of problem-based learning for four times. The level of compliance to the learning model was measured by observation of student and teacher activity sheets. The results of data analysis using t-test showed that problem-based learning have a significant influence on the mathematical logical thinking ability. Those results were showed by the increasing of mathematical logical thinking ability in each meeting. The analysis using the effect-size gave the result of the d value of 1,60 which means the application of problem-based learning have a high influence to the student’s mathematical logical thinking ability.